Avaliação da eficácia do programa institucional de bolsas de iniciação científica (PIBIC): estudo de caso em uma instituição federal de ensino superior (IFES). - Araújo, Adriana Muniz (2018)
The present research aims to evaluate the effectiveness of the Institutional Program of Scientific Initiation Grants (PIBIC) in a federal higher education institution, the Federal Institute of Science and Technology of Ceará (IFCE), based on the perception of the scholarship holders and the research professors of the program, considering the period of 2013 to 2017. In this study, effectiveness is understood as degree of accomplishment of the objectives of a certain program, being translated by the relation between the obtained results and the projected objectives. Therefore, the proposed evaluation is based on the goal-oriented approach to evaluation, using the Ralph Tyler model, which assumes that educating would consist of generating and / or changing behavior patterns and to detect them is it is necessary to analyze the congruence between the proposed objectives of the curriculum, program or other educational object and the results achieved. Thus, the effectiveness of the program was analyzed by verifying the congruence between the objectives of PIBIC and the performance achieved. The study presents as theoretical foundation the Brazilian panorama of public policies and policies of science, technology and innovation and public educational policies, as well as the relationship between the two areas; conceptual aspects of evaluation in public management and educational evaluation, presenting program evaluation and goalfocused assessment proposed by Ralph Tyler. The study has an exploratory-descriptive nature, quantitative nature and uses the case study as a research method. It uses the structured questionnaire as a data collection instrument, which has been described and analyzed with the support of statistical methods. The results suggest the effectiveness of PIBIC, since the objectives proposed by the program have been largely achieved. There were also some limitations on the achievement of some objectives or some aspects of these objectives, which deserve special attention from the institutions responsible for the promotion and implementation of the program.